The Global Campaign turns 18: a brief review of its activities and achievements - Steiner, Timothy J.; Birbeck, Gretchen L.; Jensen, Rigmor H.; Martelletti, Paolo; Stovner, Lars Jacob; Uluduz, Derya; Leonardi, Matilde; Olesen, Jes; Katsarava, Zaza (Journal of headache and pain, 2022)
The Global Campaign against Headache, as a collaborative activity with the World Health Organization (WHO), was formally launched in Copenhagen in March 2004. In the month it turns 18, we review its activities and achievements, from initial determination of its strategic objectives, through partnerships and project management, knowledge acquisition and awareness generation, to evidence-based proposals for change justified by cost-effectiveness analysis.